The Relationship between Leadership Behavior of Principal and Organizational Culture toward Teachers Work Discipline of Public Vocational High Schools of South Tangerang - Muhammad Dahlan R; Sari Purwaningrum (Ta'dib: Jurnal Pendidikan Islam, 2016)
The relationship between leadership behavior of principal and the organizational culture with teachers work discipline of Public Vocational High School of South Tangerang. A field research is aimed to find out the relationship between behavior leadership of principal and organizational culture with teacher’s work discipline of Public Vocational School of South Tangerang. The result of the research shows that: First, there is a positive relationship between the behavior leadership of principal with teacher’s work discipline. The result of correlation analysis between two research variables is gained that the relationship between behavior leadership of principal and teacher’s work discipline which is calculated by Pearson correlation is gained correlation coefficient value was 0.533. The value of determination coefficient in this analysis is gained 0.284, its means 28.4%. The variable of teacher’s work discipline can be explained from behavior leadership variable. The regression line is Ŷ = 75,735 + 0,670 X1. Second, there is a positive relationship between organizational cultures to teacher’s work discipline. The result of correlation analysis between to research variables is gained that the value of the relationship between organizational culture and teacher’s work discipline is calculated by Pearson correlation, and it is gained coefficient of correlation value 0.487 as many. The coefficient of determination’s value in this analysis is gained 0.238 which means 23.8 %. The variable of teacher’s work discipline can be explained by the variable of organizational culture. The regression line is Ŷ = 75,792 + 0,592 X2. Third, there is a positive relationship between behavior leadership of principal and organizational culture simultaneously to teacher’s work discipline is calculated by Pearson correlation and its gained coefficient correlation value 0.624 as many, then it is gained the determination of coefficient’s value 0.390 as many, which means 39 % the variable of organizational culture. The regression line is Ŷ = 47,812 + 0,522 X1 + 0,402 X2. Based on the result of the research we may say that behavior leadership of principal (X1), organizational culture (X2) have the relationship with teacher’s work discipline (Y). According to general criteria there is a relationship between behavior leadership of principal and organizational culture towards teacher’s work discipline at Public Vocational High School of South Tangerang. Hubungan antara perilaku kepemimpinan kepala sekolah dan budaya organisasi dengan disiplin kerja guru dari SMK Tangerang Selatan. Sebuah penelitian lapangan ini bertujuan untuk mengetahui hubungan antara kepemimpinan perilaku kepala sekolah dan budaya organisasi dengan disiplin kerja guru dari SMK Tangerang Selatan. Hasil penelitian menunjukkan bahwa: Pertama, terdapat hubungan positif antara perilaku kepemimpinan kepala sekolah dengan disiplin kerja guru. Hasil analisis korelasi antara dua variabel penelitian diperoleh bahwa hubungan antara kepemimpinan perilaku kepala sekolah dan disiplin kerja guru yang dihitung dengan korelasi Pearson diperoleh nilai koefisien korelasi adalah 0,533. Nilai koefisien determinasi dalam analisis ini diperoleh 0,284, yang berarti 28,4%. Variabel disiplin kerja guru dapat dijelaskan dari variabel perilaku kepemimpinan. Garis regresi Ŷ = 75.735 + 0.670 X1. Kedua, ada hubungan positif antara budaya organisasi dengan disiplin kerja guru. Hasil analisis korelasi antara variabel penelitian diperoleh bahwa nilai hubungan antara budaya organisasi dan disiplin kerja guru dihitung dengan korelasi Pearson, dan itu diperoleh koefisien nilai korelasi sebanyak 0,487. Koefisien determinasi dalam analisis ini diperoleh 0,238 yang berarti 23,8%. Variabel disiplin kerja guru dapat dijelaskan oleh variabel budaya organisasi. Garis regresi Ŷ = 75.792 + 0.592 X2. Ketiga, ada hubungan positif antara perilaku kepemimpinan kepala sekolah dan budaya organisasi secara bersamaan dengan disiplin kerja guru dihitung dengan korelasi Pearson dan nilai koefisien korelasi yang diperoleh sebanyak 0,624, maka diperoleh penentuan nilai koefisien ini sebanyak 0.390, yang berarti 39% variabel budaya organisasi. Garis regresi Ŷ = 47.812 + 0.522 X1 + 0.402 X2. Berdasarkan hasil penelitian kita dapat dikatakan bahwa prinsip perilaku kepemimpinan (X1), budaya organisasi (X2) memiliki hubungan dengan disiplin kerja guru (Y). Menurut kriteria umum ada hubungan antara kepemimpinan perilaku kepala sekolah dan budaya organisasi terhadap disiplin kerja guru di SMK Tangerang Selatan.